1996
DOI: 10.1037/0096-1523.22.3.738
|View full text |Cite
|
Sign up to set email alerts
|

Texture segmentation along the horizontal meridian: Nonmonotonic changes in performance with eccentricity.

Abstract: In 3 experiments, subjects were required to detect the presence of a small region of disparate texture embedded in a larger background at a range of eccentricities. Detection performance always peaked several degrees from fixation. Experiment 1 showed that the location of the peak was not retinally specific; scaling the display changed the location of the performance peak. Experiment 2 showed that poor foveal performance could not be explained by cross-frequency interference; filtering out high spatial frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
94
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(109 citation statements)
references
References 31 publications
14
94
1
Order By: Relevance
“…To further probe this resolution hypothesis, we enlarged the scale of the texture. Consistent with previous findings (Gurnsey et al, 1996;Joffe & Scialfa, 1995), increasing the texture scale moved the performance peak to farther eccentricities. Moreover, the central attentional impairment changed as a function of texture scale: Performance was impaired in a larger range of central retinal locations as the scale of the texture increased.…”
Section: New York University New York New Yorksupporting
confidence: 81%
See 2 more Smart Citations
“…To further probe this resolution hypothesis, we enlarged the scale of the texture. Consistent with previous findings (Gurnsey et al, 1996;Joffe & Scialfa, 1995), increasing the texture scale moved the performance peak to farther eccentricities. Moreover, the central attentional impairment changed as a function of texture scale: Performance was impaired in a larger range of central retinal locations as the scale of the texture increased.…”
Section: New York University New York New Yorksupporting
confidence: 81%
“…Instead, performance peaks at midperipheral locations and drops when the target appears at more central or farther peripheral locations. The finding that performance in this texture segregation task drops at central locations-the central performance drop-is attributed to a mismatch between the average size of spatial filters at the fovea and the scale of the texture (see, e.g., Gurnsey, Pearson, & Day, 1996;Kehrer, 1997). There is ample evidence that we process visual stimuli by means of parallel spatial filters.…”
Section: New York University New York New Yorkmentioning
confidence: 99%
See 1 more Smart Citation
“…The performance drop in the foveal area may have been due to a shift in response criterion by the participants (in the direction of more conservative response behavior), and not to a shift in sensitivity. Although Gurnsey et al (1996), for example, showed that this was not the case in their conditions, it is still necessary to ensure that this also holds for luminance stimuli. Therefore, in Experiment 2 we collected data on the false alarm rate per target position in order to be able to calculate d .…”
Section: Resultsmentioning
confidence: 99%
“…In other words, performance first increases with increasing eccentricity and-after reaching a peak-declines with further eccentricity. This pattern of results is known as the central performance drop (CPD; Kehrer, 1987Kehrer, , 1989; see also, e.g., Gurnsey, Pearson, & Day, 1996;Joffe & Scialfa, 1995;Morikawa, 2000; and is mainly observed in texture segmentation tasks that use orientation differences between target and context elements.…”
mentioning
confidence: 99%